2017
DOI: 10.1111/ijcs.12384
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of food‐wasting consumers in the Czech Republic

Abstract: This paper investigates food waste at the consumer stage of the food chain. The authors conducted a questionnaire survey with 259 respondents to identify the key characteristics of food-wasting consumers and to suggest strategies to improve food-wasting behaviour. The results of the survey confirmed that the rate at which food is wasted depends on the age, economic status and education of the person managing food in a household, on the household's income per person and on total household income. Younger people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Single-person households generate more food waste than other types of households, with higher-income households and households in cities also found to waste more (Tokareva & Eglite, 2017). Filipová et al (2017) also state that consumers from higher-income households waste more as well as younger consumers and economically active consumers, while pensioners waste less than other groups. Ilakovac et al (2020) add that the age of respondents positively affected the prevention of waste, while the income level and the number of children under the age of 18 in the household had an adverse impact.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
See 2 more Smart Citations
“…Single-person households generate more food waste than other types of households, with higher-income households and households in cities also found to waste more (Tokareva & Eglite, 2017). Filipová et al (2017) also state that consumers from higher-income households waste more as well as younger consumers and economically active consumers, while pensioners waste less than other groups. Ilakovac et al (2020) add that the age of respondents positively affected the prevention of waste, while the income level and the number of children under the age of 18 in the household had an adverse impact.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Among the factors affecting the origin of food waste, demographic factors, household size, and economic activity can be delineated, as well as, last but not least, the price of food that households buy. Demographic factors such as age or gender are usually crucial in all areas of consumer behavior (Mokrysz, 2016) and should be taken into account when designing consumer education campaigns focused on changing behavior (Filipová et al, 2017). According to Talia et al (2019), the size of the household plays a fundamental role as well as the gender and education of household consumers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the target group(s) and barriers and benefits of the target behavior (e.g., Lee & Kotler, 2015;McKenzie & Mohr, 2013;Schultz, 2014) is 23 For experimental/field studies and practical evaluations in monitored settings (e.g., school, restaurant), it might be useful to review the broad literature on food consumption research and analyze the various developed and applied unobtrusive approaches to measuring food intake, e.g., by weighing food before and after consumption, direct observation (live human rating), or indirect observation (photograph analysis) (see e.g., Kenney closely related to defining target behaviors. The finding that sociodemographics (e.g., age, sex, number of children/adults in the household) predict food waste behavior irrespective of TPB constructs (Visschers et al, 2016) illustrates the importance of sociodemographic and situational and/or contextual factors in understanding consumer food waste behavior (Filipová, Mokrejšová, Šulc, & Zeman, 2017). Just recently, academic food waste research started to segment consumers into key target groups and discuss specific leverage points for these segments (e.g., Delley &Brunner, 2017;Gaiani, Caldeira, Adorno, Segrè, & Vittuari, 2017).…”
Section: Identifying Key Target Groups That Correspond To the Target mentioning
confidence: 92%
“…The scientific literature presents a somewhat obscure picture regarding the exact relationship between income and household food waste. There is evidence that low-income households waste less food [44,[72][73][74], which might be explained by resource scarcity [10]. However, Setti [75] demonstrated that mid-to-low-income consumers wasted more food compared to low-and high-income consumers.…”
Section: Hypothesis 10 (H10)mentioning
confidence: 99%